Star Wars year by year a visual history. - Hidalgo, Pablo; Wallace, Daniel 1970-; Windham, Ryder (Dorling Kindersley Limited, 2016)
The definitive history of "Star Wars" chronicling four decades of the world of "Star Wars"; decade by decade, year-by-year, month-by-month. Everything is covered, from the influences and creation of all six "Star Wars" movies, to the toys, books and video games that have shaped the "Star Wars" dynasty. The month-by-month format is brought to life by images from the movies, TV series, comic books and more.